Analisis Perlindungan Hukum Korban Kehilangan Data dan Akun Pribadi melalui Broadcast Whatsapp (Studi Pasal 32 Undang-Undang Nomor 11 Tahun 2016 tentang Informasi dan Transaksi Elektronik) - Imelta Santalova Wanmea Susanto (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
The rapid development of information and communication technology has led to an increase in cybercrimes, particularly phishing attacks targeting personal data and online accounts. One of the most common modes occurs through broadcast messages on WhatsApp, where victims lose access to their accounts and sensitive information after opening malicious files or links. This study aims to analyze the legal protection for victims of data and account loss through WhatsApp broadcasts based on Article 32 of Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE Law). Using a normative and empirical juridical approach, data were collected through literature studies and interviews with investigators from the Special Criminal Investigation Directorate of the Lampung Regional Police. The results indicate that although Articles 30, 32, and 35 of the ITE Law provide a partial legal framework, they do not comprehensively regulate phishing activities, leading to legal uncertainty for victims. The study recommends that the government harmonize the ITE Law with the 2022 Personal Data Protection Law and strengthen preventive measures through public education and digital security awareness programs.